KHẢO SÁT HÀM LƯỢNG FLAVONOID TỔNG SỐ VÀ HOẠT TÍNH CHỐNG GỐC TỰ DO CỦA CAO CHIẾT TỪ MỘT SỐ LOẠI ĐẬU TRÊN THỊ TRƯỜNG VIỆT NAM - Nguyễn, Thị Thu Thuỷ; Đào, Nguyên Mạnh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
TOTAL FLAVONOID CONTENT AND FREE RADICAL SCAVENGING ACTIVITY OF EXTRACTS FROM SEVERAL TYPES OF BEANS ON THE MARKET IN VIETNAM Total flavonoid content and DPPH free radical scavenging activity of extracts from four types of bean, such as Vigna radiata, Vigna angularis, Vigna unguiculata, and Phaseolus vulgaris, in the market have been evaluated. The extracts from Phaseolus vulgaris had significantly higher flavonoid contents than the three other ones and showed a considerable free radical scavenging effect.